Protective Effect of Insulin in Mouse Nasal Mucus Against Olfactory Epithelium Injury - Kikuta, Shu; Kuboki, Akihito; Yamasoba, Tatsuya (Frontiers in Neural Circuits, 2021)
Insulin is present in nasal mucus and plays an important role in the survival and activity of individual olfactory sensory neurons (OSNs) via insulin receptor-mediated signaling. However, it is unclear whether insulin acts prophylactically against olfactotoxic drug-induced olfactory epithelium (OE) injury, and whether the degree of damage is affected by the concentration of insulin in the nasal mucus. The apoptosis-inducing drug methimazole was administered to the nasal mucus of diabetic and normal mice along with different concentrations of insulin. Immunohistochemical analysis was used to assess the relationship between damage to the OE and the mucus insulin concentration and the protective effect of insulin administration against eosinophilic cationic protein (ECP)-induced OE injury. Diabetic mice had lower concentrations of insulin in their nasal mucus than normal mice (diabetic vs. normal mice, p < 0.001). Methimazole administration reduced the number of OSNs in normal mice and had a more marked effect in diabetic mice. However, unilateral insulin administration prevented the methimazole-induced reduction in the number of OSNs on the ipsilateral side but not on the contralateral side (OSNs; Insulin vs. contralateral side, p < 0.001). Furthermore, intranasal ECP administration damaged the OE by inducing apoptosis (OSNs; ECP vs. contralateral side, p < 0.001), but this damage was largely prevented by insulin administration (OSNs; Insulin + ECP vs. contralateral side, p = 0.36), which maintained the number of mature OSNs. The severity of methimazole-induced damage to the OE is related to the insulin concentration in the nasal mucus (Correlation between the insulin concentration in nasal mucus and the numbers of OSNs, R2 = 0.91, p < 0.001), which may imply that nasal insulin protects OSNs and that insulin administration might lead to the development of new therapeutic agents for ECP-induced OE injury.